A translational journey: Orhan Pamuk in english - Yılmaz, Melike. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
The purpose of the present study is to examine the factors instrumental in the translational journey of Orhan Pamuk into English. Orhan Pamuk, who has been established in Turkey as a distinct literary figure since the late 1970s, now stands as the second most translated Turkish writer into English (after Yaşar Kemal). His novels have been readily translated into English in priority over many other works of Turkish literature. First reviewing Turkish literature in English translation and then Orhan Pamuk's literary career and the literary features of his novels, the study then focuses upon the question why his novels have been selected for translation into English. In order to answer this question, a corpus of reviews and critical essays in English on Pamuk and his novels, as well as interviews are examined. Such an analysis is based on the rationale that reviewers, critics and translators (considered rewriters by André Lefevere), having substantial manipulative power in the reception of an author or a literary work in a literary system, may provide key information on the factors. The examination of the corpus reveals three main factors. These factors are indeed those usually foregrounded by reviewers and critics. The first factor is the literary value of his works, the second is the juxtaposition of the dichotomy of East and West in his novels to create a synthesis, and the third and the last is his social and political awareness in regard to issues such as human rights, freedom of expression, terrorism and politics, whether national or universal.
Keywords: Turkish literature -- History and criticism.